Endodontic considerations on the variations of the anatomy of the mandibular premolars - Panagiotis Gakis; Eleftherios-Terry R Farmakis (Wolters Kluwer Medknow Publications, 2013)
Objectives: This article investigates the internal and external morphological variability of mandibular premolars along with clinical and radiographical signs that leads to early identification of these cases. Materials and Methods: The authors identified articles by searching the PubMed, Medline and Scopus databases. Inclusion criteria were case reports of mandibular premolars with aberrant internal and external anatomy, articles that describe the origin of anatomy of mandibular premolars, the traits that may influence their external and internal variability through species revolution and articles of new technologies like cone beam computed tomography that help the diagnosis of difficult cases. Results: In the majority of the cases, mandibular premolars are reported to have one root canal running a single root. On the other hand, anatomic irregularities in this group of teeth, such as the existence of more than one root or more than one root canals or even a more complicated root canal system cannot be considered infrequent as it appears in 10-25% of the cases. Conclusion: Successful endodontic treatment of mandibular premolars is a challenge for the clinician as they often present morphological and anatomical abnormalities.